GNAS locus: bone related diseases and mouse models - Yang, Wan; Zuo, Yiyi; Zhang, Nuo; Wang, Kangning; Zhang, Runze; Chen, Ziyi; He, Qing (Frontiers in Endocrinology, 2023)
GNASis a complex locus characterized by multiple transcripts and an imprinting effect. It orchestrates a variety of physiological processes via numerous signaling pathways. Human diseases associated with the GNAS gene encompass fibrous dysplasia (FD), Albright’s Hereditary Osteodystrophy (AHO), parathyroid hormone(PTH) resistance, and Progressive Osseous Heteroplasia (POH), among others. To facilitate the study of the GNAS locus and its associated diseases, researchers have developed a range of mouse models. In this review, we will systematically explore the GNAS locus, its related signaling pathways, the bone diseases associated with it, and the mouse models pertinent to these bone diseases.